(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2023)
The paper shows a significant contribution to analytical calculations of half-bridge and full-bridge inverter parameters, aiming to facilitate the operating process itself while designing systems like these. Attempts have been made within the well-known literature to precisely calculate the waveforms of characteristic currents and voltages of the inverter. Due to its complexity, exact explicit analytical forms have yet to be found, but instead, approximate forms were found. Large formulae for inverter currents and voltages prevented them from being used as an inverter project solution. The paper deals with simple analytical dependences for inverters, with a necessary accuracy from the aspect of engineering practice, that can also be directly implemented into calculations for characteristic inverter components and parameters. To confirm the new analytical expressions and method, the paper presents two interesting inverters that can be applied.